A novel mode-division (de)multiplexer with degenerate modes output for MIMO-FREE applications - Xing, Huadong; Su, Yingqun; Gao, Yan; Li, Xin; Zheng, Hongjun; Bai, Chenglin; Hu, Weisheng; Xu, Hengying (Frontiers in Physics, 2022)
In this invited paper, we propose a novel three-dimensional architecture mode (de)multiplexer with the degenerate modes output using the pure silica FMF ring core transmission channel, which solve the problem caused by the random mode rotation and can be used in the multiple-input multiple-output free (MIMO-FREE) applications such as data center application in the future. By using the pure silica FMF ring core transmission channel and larger effective refractive index difference, the performance with the low loss, the high extinction ratio (ER) and low crosstalk are achieved. That the main channel with few mode fiber (FMF) ring-core structure supports the modes LP01, LP11 and LP21, and the large effective refractive index difference between each mode in the core ensures low crosstalk characteristics between the modes. Using the pure silica core channel can effectively reduce propagation attenuation and fusion loss. Our proposed MUX/DEMUX with the degenerate modes output are achieved when the degenerate modes LP11a/LP11b and LP21a/LP21b are respectively transmitted as two independent mode signals, which can be used in the MIMO-FREE applications. The extinction ratios (ERs) of the degenerate modes LP11 and LP21 are kept above 31.66 dB and 24.43 dB, respectively, and the ER of the mode LP01 is kept above 38.72 dB in the C band. The coupling efficiency of mode LP01 is approximately 0 dB, which is almost unchanged with the increase of the wavelength. The coupling efficiency of LP11 is higher than -3.49 dB and that of LP21 is higher than -7.24 dB in the whole C-band. At 1550 nm, the coupling efficiencies of the modes LP01, LP11 and LP21 are -0.002 dB, -0.052 dB, -0.178 dB, respectively. The coupling efficiency and ER of LP01 mode are the best, those of the degenerate mode LP11 is always better than those of the modes LP21. Our proposed MUX/DEMUX achieves low crosstalk and high ER performance and solves the problem caused by the degenerate modes rotations during transmission.